Eksistensi Tengkulak dalam Menunjang Perekonomian Petani Jagung di Desa Juriya, Kecamatan Bilato, Kabupaten Gorontalo - Agu, Wawan; Musa, Farid Th.; Tanipu, Funco (Department of Sociology, Faculty of Social Sciences, Gorontalo State University, Indonesia, 2023)
The problems faced by corn farmers in Juriya Village are the same as those of farmers in general, namely problems with capital, marketing, inadequate facilities and unstable market prices, so that farmers really need help from middlemen who provide all the needs of farmers. This research is to find out how the existence of middlemen in supporting the economy of corn farmers in Juriya Village, Bilato District, Gorontalo Regency. The method used in this research is a qualitative descriptive approach. Data collection techniques in this study using observation techniques, interviews and documentation. The results showed that: First, the existence of middlemen in Juiya Village, Bilato District, Gorontalo Regency is very helpful to the farmer’s economy such as needs, both in terms of primary needs and secondary needs so that the farmers always depend on middlemen or bosses for their lives. Second, the factors that cause farmers to depend on middlemen in Juriya Village include lack of capital, fulfillment of needs, cooperation, trust, and inadequate facilities. Third, both middlemen and corn farmers have their own ways of maintaining their working relationship. Fourth, the effects of a farmer’s dependence on middlemen include a rise in dependency, exploitation of corn prices by middlemen, and inequality.